Users motivation to take part in the sharing economy in Turkey: a chaperone to sustainable consumption - Hoq, K M Rezwanul (My University, 2017)
Son iki yüzyılda dünyada bilim ve teknolojide daha önce hiç görülmeyen bir büyüme görüldü. ABSTRACT In the last two centuries, the world has seen growth in science and technology in a way it has never seen before.
Keywords: Ekonomi; Ekstra Motivasyon; Entrozant Motivasyon; Extrinsic Motivation; Intrinsic Motivation; İşletme; Paylaşım; Paylaşım Ekonomisi; Sustainability; Sustainable Consumption; Sürdürülebilir tüketim; Sürdürülebilir Tüketim Sharing Economy; Sürdürülebilirlik; Tüketim; Türkiye; Üretim; Yönetim